Beyond the blossoming fields - Watanabe, Jun ºichi 1933- (Richmond, U.K. Alma, 2008)
As a young girl from a wealthy family, Ginko Ogino seems set for a conventional life in the male-dominated society of nineteenth-century Japan. But when she contracts gonorrhea from her husband, she suffers the disgrace of divorce. Forced to bear the humiliation of being treated by male doctors, she resolves to become a doctor herself in order to treat fellow female sufferers and spare them some of the shame she had to endure. Her struggle is not an easy one--her family disowns her, and she has to convince the authorities to take seriously the very idea of a female doctor and allow her to study alongside male medical students and take the licensing exam. Based on the real-life story of Ginko Ogino--Japan's first female doctor.--From publisher description.
Originally published: Tokyo : Kawade ShoboÃÑ Shinsha, 1970.
Translation of: Hanauzumi.
Keywords: Ogino, Ginko -- 1851-1913 -- Fiction; Women physicians -- Japan -- Fiction; Japan -- History -- 19th century -- Fiction; Japan -- Social conditions -- Fiction; Biographical fiction